2017
DOI: 10.1111/1346-8138.14160
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic criteria, severity classification and guidelines of eosinophilic fasciitis

Abstract: We established diagnostic criteria and severity classification of eosinophilic fasciitis because there is no established diagnostic criteria or widely accepted severity classification of the disease. Also, there has been no clinical guideline for eosinophilic fasciitis, so we established its clinical guideline ahead of all over the world. In particular, the clinical guideline was established by clinical questions based on evidence-based medicine according to the New Minds Clinical Practice Guideline Creation M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 61 publications
0
62
0
3
Order By: Relevance
“…In regard to therapy, data from retrospective studies increasingly favor the combination of systemic corticosteroids (prednisone 0.5-1 mg/kg/day) and methotrexate (10-25 mg once weekly) as the initial treatment [14]. A study showed that patients had a response rate of more than 70% to oral prednisone [15].…”
Section: Discussionmentioning
confidence: 99%
“…In regard to therapy, data from retrospective studies increasingly favor the combination of systemic corticosteroids (prednisone 0.5-1 mg/kg/day) and methotrexate (10-25 mg once weekly) as the initial treatment [14]. A study showed that patients had a response rate of more than 70% to oral prednisone [15].…”
Section: Discussionmentioning
confidence: 99%
“…To date, various treatments have been tried in steroid‐resistant cases, most of them with anecdotal evidence to support their use (methotrexate being an exception). These include mycophenolate mofetil, cyclosporin, azathioprine, cyclophosphamide, dapsone, ketotifen, cimetidine, infliximab, and antimalarials (Fett & Arthur, ; Jinnin et al, ; Mazori et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Women are 1.3-2.1 times as likely as men to be affected (Mazori et al, 2017). A previous history of intense physical exertion or trauma has classically been considered as a triggering event (Fett & Arthur, 2018;Romano et al, 2003), but more recent studies suggest that physical stress may be less of a risk factor than previously thought (Jinnin et al, 2018;Mazori et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophilic fasciitis, or Shulman syndrome, is a rare scleroderma‐like disorder that was first described in 1975 as a variant of scleroderma with eosinophilia and fasciitis; it is characterised by symmetrical and painful swelling, progressive induration, thickening of the skin, peripheral eosinophilia, hypergammaglobulinemia and an elevated erythrocyte sedimentation rate (ESR) . Eosinophilic myositis is characterised by lymphoplasmacytic muscle infiltration, which is rarely observed.…”
Section: Introductionmentioning
confidence: 99%